A Comprehensive Review of Regulatory Requirements and Registration Process of Pharmaceutical Drug Products in CIS Countries - Pihwal, Kapil; Pawar, Neelam; Aamir, Sheikh; Alam, Mohammad S.; Rathee, Vikas (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2020)
Background: The CIS region has a potential market for India. The registration of the drug products in CIS regions is a challenging task because these countries have no harmonized regulatory organization. The CIS region includes 12 countries such as Russia, Kyrgyzstan, Ukraine, Uzbekistan, Kazakhstan, Tajikistan, Turkmenistan, Armenia, Azerbaijan, Belarus, Georgia and Moldova, which require different regulatory guidelines for medicinal product registration as per their FDA guidelines. The different guidelines for the same region become a challenging task for the manufacturer and exporter. The registration of the same product for different countries of CIS is not possible with the same dossier due to the lack of their regulatory harmonization. These countries obey their country-specific dossier format, so to target these market manufacturers and exporters needs to submit different dossier documents for different countries. But Ukraine and Kazakhstan have harmonization and it varies in Uzbekistan and Tajikistan. Ukraine and Kazakhstan are also imposing strict rules and expecting USFDA level documents for approval. Conclusion: The overall conclusion is that harmonization in CIS is highly imbalanced, which affects both time and cost for product registration. Harmonization is the need of the era for easy product registration, and it will be beneficial for the manufacturer, regulator, importer, exporter, and to access medicines of high public health value.
Keywords: CIS region